1999
DOI: 10.1046/j.1365-2672.1999.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen delivery by attenuated Bacillus anthracis: new prospects in veterinary vaccines

Abstract: This report summarizes the recent investigations on the use of Bacillus anthracis as a live vector for delivery of antigens. Recombinant strains were constructed by engineering the current live Sterne vaccine. This vaccine, used to prevent anthrax in cattle, causes side‐effects due to anthrax toxin activities. Bacteria producing a genetically detoxified toxin factor were devoid of lethal effects and were as protective as the Sterne strain against experimental anthrax. Moreover, B. anthracis expressing a foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The feasibility of expressing foreign proteins in strain RB51 makes it a strong candidate vector for the development of a live, attenuated multivalent vaccine that can provide simultaneous protection against brucellosis and infection with heterologous pathogens, such as Mycobacterium spp. Recently, several attenuated bacterial strains, including B. abortus strain 19, have been used for the expression of heterologous proteins (8,11,12,17,38,41). However, strain RB51 has many advantages over all other live bacterial vectors for use in several domestic and wild animals where vaccination against brucellosis is required.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of expressing foreign proteins in strain RB51 makes it a strong candidate vector for the development of a live, attenuated multivalent vaccine that can provide simultaneous protection against brucellosis and infection with heterologous pathogens, such as Mycobacterium spp. Recently, several attenuated bacterial strains, including B. abortus strain 19, have been used for the expression of heterologous proteins (8,11,12,17,38,41). However, strain RB51 has many advantages over all other live bacterial vectors for use in several domestic and wild animals where vaccination against brucellosis is required.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of a safe and effective animal vaccine, a recently proposed model for the global distribution and suitability of anthrax found that most livestock and wildlife at risk of exposure are not vaccinated [26]. This may be due to the fact that most commercial animal vaccines use the same formulation developed by Max Sterne in 1939 which is outdated, can cause adverse reactions, requires yearly boosters and requires refrigerated storage [27,28]. The most prominent reason, however, is because the existing method of subcutaneous injection with the Sterne vaccine is not a feasible method of vaccination for free-ranging livestock and wildlife, so many anthrax vaccine reviews have called for a new anthrax vaccine, specifically an oral anthrax vaccine [8,12,27].…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%
“…This may be due to the fact that most commercial animal vaccines use the same formulation developed by Max Sterne in 1939 which is outdated, can cause adverse reactions, requires yearly boosters and requires refrigerated storage [27,28]. The most prominent reason, however, is because the existing method of subcutaneous injection with the Sterne vaccine is not a feasible method of vaccination for free-ranging livestock and wildlife, so many anthrax vaccine reviews have called for a new anthrax vaccine, specifically an oral anthrax vaccine [8,12,27]. Sharing in that opinion are ranch managers in the Edwards Plateau region of Texas who cannot practically vaccinate all of their animals by injection, so some have improvised by pouring the Sterne vaccine over feed, even doing so every other week for the entire spring before the typical anthrax season by one account.…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%
“…However, due to toxin production this live vaccine Sterne strain can still elicit severe side effects such as fever, severe oedema or even death. Recently, the Steme strain was manipulated in order to decrease the virulence of the vaccine and it was shown that attenuated B. anthracis can be used for the design of new live vaccines against other veterinary diseases by expressing a foreign antigen (Brossier et al, 1999).…”
Section: Gram-positive Bacteria Used Us Antigen Delivery Systemsmentioning
confidence: 99%